Precise Molecular Design for High-Performance Luminogens with Aggregation-Induced Emission - Xu, Shidang (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.